2014
DOI: 10.1084/jem.20130627
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative metabolism enables Salmonella evasion of the NLRP3 inflammasome

Abstract: Salmonella lacking the TCA enzyme aconitase trigger NLRP3 inflammasome activation in infected macrophages, leading to elevated inflammatory responses and reduced virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 109 publications
(184 reference statements)
5
71
0
Order By: Relevance
“…4D). Consistent with our findings, a recent study reported that the NLRP3 inflammasome was activated by the mitochondrial superoxide induced during S. Typhimurium infection of BMDMs (50). Under curliinducing conditions, the flagellin mutant did not have a profound effect on IL-1␤ production (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…4D). Consistent with our findings, a recent study reported that the NLRP3 inflammasome was activated by the mitochondrial superoxide induced during S. Typhimurium infection of BMDMs (50). Under curliinducing conditions, the flagellin mutant did not have a profound effect on IL-1␤ production (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…It is likely that during Salmonella infection, multiple receptors are engaged in tandem, generating a mixed response that is evident in the in vivo mouse models. In addition, Salmonella that lacks aconitase has attenuated virulence that is dependent on rapid NLRP3 inflammasome activation [81]. Neutrophils can also activate the NLRC4 inflammasome in response to Salmonella infection and make IL-1β but do not undergo pyroptosis (in contrast to macrophages) leading to sustained IL-1β production [82].…”
Section: Pathogens Differentially Interfere With the Inflammasomes Anmentioning
confidence: 99%
“…S. typhimurium has also developed mechanisms to evade NLRP3 inflammasome activation by utilizing the TCA enzymes aconitase (acnB) and isocitrate dehydrogenase (icdA). Interestingly, acnB and icdA mutants induced rapid NLRP3 inflammasome activation through a process that resulted in elevated bacterial citrate and increased mitochondrial reactive oxygen species (34).…”
Section: Bacterial Effector Molecules That Facilitate Evasion Of Inflmentioning
confidence: 99%